A qualitative study on maternal anxiety over pediatric dental treatment during the coronavirus disease 2019 (COVID-19) pandemic: Implications for future pandemics - Setyowati, Dini; Santoso, Richard Kevin; Kamila, Nurul Naswaa; Ulhaq, Aqilah Dhiya (Majalah Kedokteran Gigi Indonesia, 2024)
The coronavirus disease 2019 (COVID-19) has introduced new impediments to delivering and accessing dental care. In light of the COVID-19 pandemic experience, research into anticipatory measures for pediatric dental care is necessary to prepare for future pandemics or other public health events. This study sought to explore factors influencing mothers’ anxiety over taking their children to the dentist during the COVID-19 pandemic. We conducted an explorative qualitative study with social cognitive theory (SCT) as its theoretical framework. In-depth interviews with mothers of children aged 6–12 years in five areas in Surabaya were selected as the method for answering the qualitative inquiries. To improve transparency, we employed a 32-item consolidated criteria for reporting qualitative research (COREQ) checklist. Thematic data analysis revealed three primary cross-cutting themes: internal (personal) factors, external (socio-environmental) factors, and interaction between internal factors and external factors. Based on the interviews, five internal factor sub-themes impacting maternal anxiety over child dental treatment emerged: knowledge, self-efficacy, risk perception, trust in a dentist, and experiences with a child’s dental visit. Moreover, three external factor sub-themes were noted: public transportation, bulk COVID-19 information, and costs. Findings revealed that internal and external factors interacted with each other and influenced maternal anxiety over pediatric dental care during the COVID-19 pandemic. This study benefits public health by contributing to the development of strategies and policies for dental health services under unforeseen health crises.